Association between triglyceride–glucose index and its derivatives and lung adenocarcinoma risk: a case–control study in Chinese adults - Qiu, Pengcheng; Xie, Jinshi; He, Yayuan; Cong, Rizheng; Huang, Keyue; Huang, Bo (Frontiers in Endocrinology, 2025)
Background and objectivesLung cancer is the leading cause of cancer-related death worldwide, and China accounts for nearly one-third of global cases and deaths. Insulin resistance (IR) has been implicated in cancer development, but evidence for its association with lung adenocarcinoma remains inconsistent, especially in Asian populations. The triglyceride–glucose (TyG) index and its derivatives are simple surrogate markers of IR. This study aimed to examine the associations between the TyG index, its derivatives (TyG-BMI, TyG-WC, TyG/HDL-C), and lung adenocarcinoma risk in Chinese adults.MethodsWe conducted a case–control study including 200 histologically confirmed lung adenocarcinoma patients and 500 age- and sex-matched healthy controls from the First Affiliated Hospital of Jinzhou Medical University (September 2023–September 2024). Anthropometric and biochemical measurements were obtained using standardised protocols. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for age, BMI, and smoking status. Restricted cubic spline (RCS) analysis assessed dose–response patterns, and receiver operating characteristic (ROC) curves evaluated predictive performance.ResultsLung cancer patients had significantly higher TyG index and derivative values, as well as higher systolic blood pressure, HbA1c, LDL-C, and TC levels compared with controls (all P < 0.05). RCS analysis showed generally linear positive associations between all TyG-related indices and lung cancer risk, with the steepest increase for TyG/HDL-C. ROC analysis indicated that the TyG/HDL-C ratio achieved the highest predictive performance among the evaluated markers, with an AUC of 0.851.ConclusionThe TyG index and its derivatives are positively associated with Lung adenocarcinoma risk in Chinese adults, with the TyG index demonstrating the greatest predictive performance. These easily obtainable metabolic markers may serve as low-cost tools for identifying individuals at elevated risk of Lung adenocarcinoma. Prospective studies are warranted to confirm these findings and explore underlying biological mechanisms.